Human alpha-defensin-1 protects cells from intoxication with Clostridium perfringens iota toxin. Issue 2 (12th March 2018) - Fischer, Stephan; Popoff, Michel R; Barth, Holger
Abstract: Iota toxin is produced by Clostridium perfringens type E strains and associated with diarrhea in cattle and lambs. This binary protein toxin comprises the enzyme component iota a (Ia), which ADP-ribosylates G-actin, and the separate transport component iota b (Ib), which delivers Ia into the cytosol of target cells. Ib binds to cell receptors and forms biologically active toxin complexes with Ia, which cause rounding of adherent cells due to the destruction of the actin cytoskeleton. Here, we report that the human peptide α-defensin-1 protects cultured cells including human colon cells from intoxication with iota toxin. In contrast, the related ß-defensin-1 had no effect, indicating a specific mode of action. The α-defensin-1 did not inhibit ADP-ribosylation of actin by Ia in vitro . Pretreatment of Ib with α-defensin-1 prior to addition of Ia prevented intoxication. Additionally, α-defensin-1 protected cells from cytotoxic effects mediated by Ib in the absence of Ia, implicating that α-defensin-1 interacts with Ib to prevent the formation of biologically active iota toxin on cells. In conclusion, the findings contribute to a better understanding of the functions of α-defensin-1 and suggest that this human peptide might be an attractive starting point to develop novel pharmacological options to treat/prevent diseases associated with iota toxin-producing Clostridium perfringens strains. Abstract : The human body-own peptide α-defensin-1 neutralizes iota toxin from Clostridium perfringens and protects human cells from this protein toxin, which might offer novel therapeutic options.